Simulation-based approach to lean manufacturing - Effendi Mohamad; Mohd.Amri Sulaiman (Monograph series, 2017)
Lean Manufacturing (LM) has been applied to various manufacturing sectors, and has gained particular acceptance and momentum over the past few decades. However, the implementation of LM is not always successful due to a number of reasons. Firstly, there is a general lack of understanding of lean concepts as well as a lapse of proficiency in the selection of appropriate LM tools, inappropriate employee attitude on the shop floor, a lack of LM experts within companies, difficultly in implementing concepts due to a lack of support, and an inability of LM tools to address various independent processes in the production line